A Novel Small Molecule p53 Stabilizer for Brain Cell Differentiation - Amaral, Joana D.; Silva, Dário; Rodrigues, Cecília M. P.; Solá, Susana; Santos, Maria M. M. (Frontiers in Chemistry, 2019)
Brain tumor, as any type of cancer, is assumed to be sustained by a small subpopulation of stem-like cells with distinctive properties that allow them to survive conventional therapies and drive tumor recurrence. Thus, the identification of new molecules capable of controlling stemness properties may be key in developing effective therapeutic strategies for cancer by inducing stem-like cells differentiation. Spiropyrazoline oxindoles have previously been shown to induce apoptosis and cell cycle arrest, as well as upregulate p53 steady-state levels, while decreasing its main inhibitor MDM2 in the HCT116 human colorectal carcinoma cell line. In this study, we made modifications in this scaffold by including combinations of different substituents in the pyrazoline ring in order to obtain novel small molecules that could modulate p53 activity and act as differentiation inducer agents. The antiproliferative activity of the synthesized compounds was assessed using the isogenic pair of HCT116 cell lines differing in the presence or absence of the p53 gene. Among the tested spirooxindoles, spiropyrazoline oxindole 1a was selective against the cancer cell line expressing p53 and presented low cytotoxicity. This small molecule induced neural stem cell (NSC) differentiation through reduced SOX2 (marker of multipotency) and increased III-tubulin (marker of neural differentiation) which suggests a great potential as a nontoxic inducer of cell differentiation. More importantly, in glioma cancer cells (GL-261), compound 1a reduced stemness, by decreasing SOX2 protein levels, while also promoting chemotherapy sensitization. These results highlight the potential of p53 modulators for brain cell differentiation, with spirooxindole 1a representing a promising lead molecule for the development of new brain antitumor drugs.